Difference of learning mathematics between open question model and conventional model - Afandi, Ahmad (Universitas Malikussaleh, Aceh Utara, Indonesia, 2018)
Open learning model as well as conventional learning model is a learning model that is able to enable students in acquiring knowledge and learning experiences. The purpose of this research is to know the difference of learning result between students taught by using model of open matter problem and conventional learning model on the subject of wake up space. This research was conducted at SMP Al Badri Arjasa Jember in February 2018. The research subjects were 70 students in two classes namely class VIII - A and class VIII - B. This research uses experimental design that is, one experiment class and one control class. The results obtained in the study are learning outcomes using open-ended learning model and conventional learning model. T-test conducted shows that there are differences. Average learning outcomes of experimental class students after treatment was 69.657 while the control class learning outcome was 56.886. The conclusion that can be drawn from data analysis and discussion result is difference of student learning result by using model of open learning problem with conventional learning model, and model of open learning problem is suitable to be applied to the subject of student room of SMP Al Badri Arjasa Jember.